DSLR Cinema : a beginner's guide to filmmaking on a budget - Lancaster, Kurt (New York : Routledge, Taylor & Francis Group, 2018)
The DSLR cinema revolution began over ten years ago. Professional filmmakers, students, video journalists, event video shooters, production houses, and others jumped at the opportunity to shoot cinematic images on these low budget cameras. The first edition of the book mapped the way focusing exclusively on DSLRs. This new edition shows how you can create stunning cinematic images using low budget cinema cameras, from iPhones to the C200. The author examines new cameras and new projects as filmmakers shoot action movies with the Panasonic GH5, craft personal stories with Blackmagic's Pocket Cinema Camera, make documentaries and short films with the Canon C100 Mark II, and create music videos and documentaries with the Canon's 5D Mark IV. This book, like the previous editions, takes the wisdom of some of the best shooters and empowers you to create visually stunning images with low budget cinema cameras. It includes six all-new case studies, as well as updated examples from short films and documentaries. DSLR Cinema contains the essential tools to make you a better visual storyteller.
Foreword / Shane Hurlbut -- Introduction : The rise and fall of the DSLR cinema revolution -- Composition, lenses, blocking, and camera movement -- Lighting -- Exposure -- Recording quality audio -- Key concepts in postproduction workflow -- Telling better stories -- Cinematic gear on a budget -- David Tembleque: Blackmagic's pocket cinema camera in Dear Tom -- Joe Simon: Canon's C100 Mark II in Fragments / Dana Beasley -- Philip Bloom: Canon's 7D in A day at the races -- Kiril Kirkov: documentary intimacy with the Canon 5D Mark III in Art of the people -- Po Chan and Shane Hurlbut: Canon's 5D Mark II in The last 3 minutes -- J. Van Auken: filming action with Panasonic's GH5 in Unmasked -- Mari Cleven: filming documentaries on the Canon C100 Mark II -- Bibbi Abruzzini: filming documentaries on the Canon 5D Mark IV.
Includes index.
Keywords: DIGITAL CINEMATOGRAPHY